An overview of drug delivery vehicles for cancer treatment: Nanocarriers and nanoparticles including photovoltaic nanoparticles - Chowdhury, Silvia; Yusof, Faridah; Wan Salim, Wan Wardatul Amani; Sulaiman, Nadzril; Faruck, Mohammad Omer (ELSEVIER, 2016)
Cancer is a complicated disease for which finding a cure presents challenges. In recent decades, new ways to treat cancer are being sought; one being nanomedicine, which manipulates nanoparticles to target a cancer and release drugs directly to the cancer cells. A number of cancer treatments based on nanomedicine are under way and mostly are in preclinical trials owing to challenges in administration, safety, and effectiveness. One alternative method for drug delivery is the use of photovoltaic nanoparticles,which has the potential to deliver drugs via light activation. The concepts are based on standard photovoltaic cell that holds opposite charges on its surfaces and releases drugs when charge intensity or polarity changes upon photo-stimulation such as from a laser source or sunlight. This review will cover some recent progress in cancer treatment using nanoparticles, including photovoltaic nanoparticles.